Are people with lower limb amputation changing? A seven-year analysis of patient characteristics at admission to inpatient rehabilitation and at discharge. Issue 26 (18th December 2019) - Batten, Heather; Kuys, Suzanne; McPhail, Steven; Varghese, Paulose; Mandrusiak, Allison
Abstract: Purpose: What are the characteristics of people with lower limb amputation at admission to, and discharge from, subacute rehabilitation? Have these characteristics changed over time? Methods: A total of 425 lower limb amputation inpatient rehabilitation admissions (335 individuals) from 2005 to 2011 were examined. Admission characteristics, including aetiology, gender, age, amputation level, cognition (Mini-Mental State Examination (MMSE)), indoor mobility aid, motor function (Functional Independence Measure motor subscale) and number and type of comorbidities, and discharge characteristics, including prosthetic prescription, motor function, discharge mobility aid, and destination were compared by admission date and year. Results: Proportion of people with lower limb amputation with nonvascular aetiology increased over time (2004, 15% to 2011, 24%) (ß = −181.836, p < 0.001). Admission cognition increased over time (ß = 9.296, p < 0.001). Motor function worsened over time; median admission (IQR) Functional Independence Measure motor 70 (59–77) in 2005 to 67 (51.5–73.25) in 2011 (ß = −1.937, p < 0.001) and discharge from 81 in 2005 to 79 in 2011 (ß = −1.267, p < 0.001). Prosthetic prescription rates were highest in 2005 (68%) decreasing to 47% in 2010 (ß = −200.473, p < 0.001). Conclusions: Total numbers of people with lower limb amputation did not change over the seven-year study period. Changes were observed in aetiology, cognition and motor function. Prosthetic prescription rates decreased over time. Implications for rehabilitation: Rehabilitation should account for the changing characteristics of people with lower limb amputation. Motor function should be addressed as part of rehabilitation to optimise the patient's ability to return home and to the community. Prescription rates for lower limb prostheses reduced across time, indicating more specific selection processes and refined clinical decision making; this decision is best informed by a multi-disciplinary approach.